2022
DOI: 10.1038/s41423-021-00812-7
|View full text |Cite
|
Sign up to set email alerts
|

Conventional type 1 dendritic cells protect against age-related adipose tissue dysfunction and obesity

Abstract: Conventional dendritic cells (cDCs) scan and integrate environmental cues in almost every tissue, including exogenous metabolic signals. While cDCs are critical in maintaining immune balance, their role in preserving energy homeostasis is unclear. Here, we showed that Batf3-deficient mice lacking conventional type 1 DCs (cDC1s) had increased body weight and adiposity during aging. This led to impaired energy expenditure and glucose tolerance, insulin resistance, dyslipidemia, and liver steatosis. cDC1 deficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 72 publications
2
11
0
Order By: Relevance
“…Importantly, high MICAB expression has been observed in SGs from pSS, 48 and polymorphism of this molecule have been linked to higher susceptibility to develop the disease, 49 . In addition, some of our data suggest that CD141+ and CD1c+ cDC might provide non-redundant signals to NK cells since we have shown that CD141+ cDC might be more effective inducing IFNg expression on NK cells or efficiently activate CD8+ T cells, as previously reported, 26, 27, 50 5, 6 . Therefore, further studies are required to better understand complex interactions between different DC subsets contributing to pSS pathology.…”
Section: Discussionsupporting
confidence: 81%
“…Importantly, high MICAB expression has been observed in SGs from pSS, 48 and polymorphism of this molecule have been linked to higher susceptibility to develop the disease, 49 . In addition, some of our data suggest that CD141+ and CD1c+ cDC might provide non-redundant signals to NK cells since we have shown that CD141+ cDC might be more effective inducing IFNg expression on NK cells or efficiently activate CD8+ T cells, as previously reported, 26, 27, 50 5, 6 . Therefore, further studies are required to better understand complex interactions between different DC subsets contributing to pSS pathology.…”
Section: Discussionsupporting
confidence: 81%
“…A recent study investigated the role of BATF3 and cDC1s in the regulation of adipose tissue homeostasis ( 99 ). The authors demonstrate that the abundance of cDC1s in visceral fat tissue is reduced in HFD fed mice and that BATF3-deficiency and the loss of cDC1 results in the development of obesity during ageing.…”
Section: Discussionmentioning
confidence: 99%
“…Mice lacking DC, due to the ablation of Flt3l or E2-2 genes, did not develop insulin resistance when fed with a high-fat diet (HFD) [ 60 , 61 ]. However, ablation of the Batf3 gene, which results in the lack of conventional DC, led to the development of insulin resistance and increased adiposity [ 62 ]. These controversial findings warrant further studies to delineate the role of specific DC populations in obesity.…”
Section: The Innate Immune System and Inflammationmentioning
confidence: 99%